Virgin Coconut Oil (VCO) Meningkatkan Epitelisasi Luka Diabetes Mellitus - Daryaswanti, Putu Intan; Widyanata, Komang Agus Jerry; Artawan, I Kadek (ProHealth Journal, 2024)
Diabetic wounds are a complication of Diabetes Mellitus (DM) which is caused by peripheral blood vessel disorders and neuropathy. Treatment for diabetic wounds is not sufficient to be treated using antibiotics, but wound care must be carried out. The important thing in wound care is time and quality to improve the healing of the procedure and to reduce the costs associated with healing. The aim of this research was to determine the effect of administering VCO on diabetic wound healing. This study used a one group pre- post test experimental design to determine differences in the degree and extent of wounds as well as wound healing time after being given VCO. The number of samples in this study was 11 people in 1 group of patients who had DM wounds. Most of the respondents were aged 56 – 65 years (54.6%) and were male (63.6%). In pre-test conditions or before being given VCO. Most of the wound area before intervention was (11.85) with the base color of the wound being red, the type of fluid being serious to haemooserous, the skin around the wound being healthy, erythema, edema and hyperpigmentation with an average of epithelium (1.82). Most of the wound areas after intervention were large (6.65) with the base color of the wound pink (epitilization), dry to serous fluid type, the skin around the wound was healthy, with an average epilation (68.64). There was a significant difference between before and after wound treatment using VCO in terms of diabetic wound area of 0.006 and wound epithelialization of 0.000 where p < 0.05. VCO can increase skin moisture which can stimulate collagen synthesis thereby accelerating epithelialization and granulation of wound tissue.